2020
DOI: 10.3390/ijerph17207394
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Hospitalised Current Smokers and COVID-19

Abstract: SARS-CoV-2 is a new coronavirus that has caused a worldwide pandemic. It produces severe acute respiratory disease (COVID-19), which is fatal in many cases, characterised by the cytokine release syndrome (CRS). According to the World Health Organization, those who smoke are likely to be more vulnerable to infection. Here, in order to clarify the epidemiologic relationship between smoking and COVID-19, we present a systematic literature review until 28th April 2020 and a meta-analysis. We included 18 recent COV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 95 publications
(161 reference statements)
4
41
0
5
Order By: Relevance
“…The low prevalence of smokers among our COVID-19 patients is remarkable. This is in line with a few publications claiming lower rates of SARS-CoV-2 infections in countries with a high prevalence of smoking, a lower number of hospitalized current smokers than expected [ 33 ] and even leading to a controversial and probably premature suggestion for considering nicotine as a therapeutic option [ 34 ]. Nicotine acts in a similar fashion as the naturally occurring neurotransmitter acetylcholine on nicotinic acetylcholine receptors and may act as an anti-inflammatory agent [ 35 ].…”
Section: Discussionsupporting
confidence: 82%
“…The low prevalence of smokers among our COVID-19 patients is remarkable. This is in line with a few publications claiming lower rates of SARS-CoV-2 infections in countries with a high prevalence of smoking, a lower number of hospitalized current smokers than expected [ 33 ] and even leading to a controversial and probably premature suggestion for considering nicotine as a therapeutic option [ 34 ]. Nicotine acts in a similar fashion as the naturally occurring neurotransmitter acetylcholine on nicotinic acetylcholine receptors and may act as an anti-inflammatory agent [ 35 ].…”
Section: Discussionsupporting
confidence: 82%
“…Immunity system is weaker in male than in female sex, therefore men are at higher risk of viral infection than women [ 22 ]. Because the low prevalence of smoking in patients hospitalized with COVID-19 [ 23 , 24 ], the protective effect of tobacco is largely discussed [ 25 ]; however, several meta-analyses of observational studies have confirmed that smoking habit is related to severe COVID-19 and adverse outcomes [ 19 , 21 , 26 28 ]. Tobacco smoking is associated with upregulation of the angiotensin-converting-enzyme-2 (ACE2), immune system disturbance, endothelial injury and hypercoagulable state [ 28 , 29 ]; these factors and pre-existing comorbidities could explain adverse outcomes observed in smokers with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Depuis la publication de cet avis, la version 4 du manuscrit a été consultée 205 196 fois (au 10 janvier 2021), et de nombreux articles publiés dans des revues classiques, sur des serveurs communautaires, ou auprès de revues dites disruptives, ont confirmé la moindre prévalence de fumeurs parmi les patients hospitalisés pour COVID-19 et se sont interrogés sur les éventuels liens entre tabac ou nicotine et COVID-19 [25] , [26] , [27] et/ou sur la communication de résultats pouvant générer des comportements individuels à risque [28] .…”
Section: Les Articlesunclassified